(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
The main objective of this work is to discuss the development of neoliberalism in Brazilian Educational system in light of its historical and theoretical framework. In order to do so, numerous pages are dedicated to the characterization of the neoliberal agenda as a historical process, political movement and ideological matrix, entangling the different aspects of this phenomenon based on its complementarities and points of friction. More than only an economical tool in order to turn public wealth into private assets, neoliberalism stands out historically as a highly sophisticated project of power, that is implemented by sections of transnational capitalism and operated by local agents whose capillarity and influence allow it to penetrate deeply in all different areas of the globe. After the construction of a panorama regarding the constitution and the development of this international oligarchic enterprise, the neoliberal invasion of Brazilian educational system, led by expedients that range from the appropriation of the public revenue to create compulsory demand for educational business conglomerates until the snatch of the public budget through private models of management in the field of Public Education. Keywords: Neoliberalism. Education Policy. Liberalism. Monetarism. Transnational Capitalism.